إستراتيجيات تعزيز الفعالية الذاتية لتخفيف من قلق الامتحان و الحد من سلوك الغش في الامتحانات لدى الطالب الجامعي - مسعودى,عفاف; عيسى,عزيزة (University of Eloued جامعة الوادي, 2025)
نسعى من خلال هذه الدراسة التعرف على استراتيجيات تعزيز الفعالية الذاتية، بناءً على نظرية ألبرت باندورا، للتخفيف من قلق الامتحان والحد من سلوك الغش بين الطلاب الجامعيين. كما يسلط البحث الضوء على أهمية تطوير الفعالية الذاتية كجزء من التدابير الوقائية والتدخلية في البيئات التعليمية لتعزيز النزاهة الأكاديمية. تشير الدراسة إلى أن استراتيجيات مثل تحديد الأهداف، التعلم القائم على النمذجة، وتقديم التغذية الراجعة الإيجابية، يمكن أن تلعب دورًا حاسمًا في تحسين الأداء الأكاديمي وتقليل القلق المرتبط بالامتحانات. Abstract: The study explores the application of self-efficacy enhancing strategies, based on Albert Bandura's theory, to alleviate test anxiety and reduce cheating behavior among undergraduate students. The study relies on training methods aimed at strengthening students' self-confidence and their abilities to overcome academic challenges without resorting to cheating. The research also highlights the importance of developing self-efficacy as part of preventive and intervention measures in educational settings to enhance academic integrity. The study suggests that strategies such as goal setting, modeling-based learning, and providing positive feedback can play a crucial role in improving academic performance and reducing exam-related anxiety
وفق نظرية ألبرت باندورا
Albert Bandura
Keywords: الفعالية الذاتية; قلق الامتحان; نظرية ألبرت باندورا; سلوك الغش; Self-efficacy; Strategy; Behavioral; Cheating